The Reconnection : Heal Others, Heal Yourself - Pearl, Eric, Dr. (Australia Hay House, Inc., 2001)
Takes you on the author's journey from the discovery of his ability to heal to his well-deserved reputation as the instrument through which a new healing process is being introduced to the world. Most importantly, this book reveals methods you can use to personally master these new healing energies.
Include Notes
Keywords: Healers -- Pearl, Eric -- California